Pulmonary shunts in severe hepatosplenic schistosomiasis: Diagnosis by contrast echocardiography and their relationship with abdominal ultrasound findings. - Liana Gonçalves-Macedo; Ana Lucia Coutinho Domingues; Edmundo Pessoa Lopes; Carlos Feitosa Luna; Vitor Gomes Mota; Mônica Moraes de Chaves Becker; Brivaldo Markman-Filho (PLOS Neglected Tropical Diseases, 2017)
Schistosomiasis is endemic to several parts of the world. Among the species that affect humans, Schistosoma mansoni is one of the most common causes of illness. In regions where schistosomiasis mansoni is endemic, reinfection is responsible for the emergence of hepatosplenic schistosomiasis (HSS) with portal hypertension in about 10% of infected individuals. Regardless of its etiology, portal hypertension may bring about the formation of arteriovenous fistulas and pulmonary vascular dilation, thus constituting a pulmonary shunt and its presence has been associated with the occurrence of neurological complications. The objective of this study was to identify pulmonary shunt using TTCE in patients with HSS and esophageal varices, and to compare the abdominal ultrasound and endoscopy findings among patients with and without pulmonary shunt.In this case series, a total of 461 patients with schistosomiasis mansoni were prospectively evaluated using abdominal ultrasound and endoscopy and 71 presented with HSS with esophageal varices. Fifty seven patients remained in the final analysis. The mean age of the patients was 55 ± 14 years, and 65% were female. Pulmonary shunts were observed in 19 (33.3%) patients. On comparing the groups with and without pulmonary shunt, no significant differences were observed in relation to the abdominal ultrasound and endoscopic findings. When comparing the two subgroups with pulmonary shunts (grade 1 vs grades 2 and 3), it was observed that the subgroup with shunt grades 2 and 3 presented with a significantly higher frequency of an enlarged splenic vein diameter (>0.9 cm), and an advanced pattern of periportal hepatic fibrosis (P = 0.041 and P = 0.005, respectively). None of the patients with pulmonary shunts had severe neurological complications.Our findings suggest that in HSS with esophageal varices the pulmonary shunts may be present in higher grades and that in this condition it was associated with ultrasound findings compatible with advanced HSS.